Exploring Medical Student Experiences of the Use of Escape Rooms as an Innovative Teaching Method Within Undergraduate Psychiatry Teaching - Hanna Mansi; Rachel Rice; Lisa Dikomitis; Sukhi Shergill; Joanne Rodda (BJPsych Open, 2025)
Aims: The study aimed to explore the experience and opinions of third year medical students regarding the use of escape rooms as a teaching modality in undergraduate psychiatry education. This research will help inform whether escape rooms have a viable role in medical education.